2004
DOI: 10.1074/jbc.r400025200
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein

Abstract: C-reactive protein (CRP) is a phylogenetically highly conserved plasma protein, with homologs in vertebrates and many invertebrates, that participates in the systemic response to inflammation. Its plasma concentration increases during inflammatory states, a characteristic that has long been employed for clinical purposes. CRP is a pattern recognition molecule, binding to specific molecular configurations that are typically exposed during cell death or found on the surfaces of pathogens. Its rapid increase in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
1,016
6
32

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,356 publications
(1,071 citation statements)
references
References 52 publications
17
1,016
6
32
Order By: Relevance
“…In addition, we demonstrated that CRP has a direct inhibitory effect on the endocytic capability of monocyte-derived DC, and this effect could be effectively blocked by anti-CRP Ab. Although other studies have shown that CRP can stimulate phagocytosis functions in macrophages [51], our results clearly show that endocytosis by DC is greatly impaired by CRP. Therefore, CRP not only inhibited DC differentiation but also directly impaired the antigen capture capacity of DC in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition, we demonstrated that CRP has a direct inhibitory effect on the endocytic capability of monocyte-derived DC, and this effect could be effectively blocked by anti-CRP Ab. Although other studies have shown that CRP can stimulate phagocytosis functions in macrophages [51], our results clearly show that endocytosis by DC is greatly impaired by CRP. Therefore, CRP not only inhibited DC differentiation but also directly impaired the antigen capture capacity of DC in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…IL-6 is an important cytokine responsible for the acute phase inflammatory response. IL-6 is known to induce the production of C-reactive protein (37,38). C-reactive protein has been identified as an important predictor of coronary heart disease (39).…”
Section: Figurementioning
confidence: 99%
“…Contrasting Approaches to the Study of Inflammation and Disease C-reactive protein (CRP) is a prototypical acute-phase protein and commonly measured biomarker of inflammation (2). The recent advent of highly sensitive laboratory assays for CRP has led to the discovery that chronic low-grade inflammation-levels of inflammation previously thought to be inconsequential-may contribute to the pathophysiology of a wide range of diseases of aging, including cardiovascular disease (CVD) (3), type 2 diabetes (4), metabolic syndrome (3), and late-life disability (5) as well as allcause mortality (6).…”
mentioning
confidence: 99%